Examining Semitic Rhetoric: A Qur’anic Sciences Perspective - Aqdi Rofiq Asnawi; Idri Idri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
In his study of Qur’anic structure, Michel Cuypers applied Semitic Rhetoric that has been used to analyze Biblical structure. Despite having received positive responses from Gabriel Said Reynolds and others, Cuypers’ method was criticized by Nicolai Sinai for ignoring rhyme in the Qur’an and overdoing in maintaining the existence of the ring structure in the Qur’an. This paper, then, attempts to examine this analytic method from the perspective of the Qur’anic sciences’ (‘ulu>m al-Qur’a>n). This study aims to determine proportionally the characteristics of the method and the effect it produces by using descriptive-analytic and comparative research methods. This paper argues that there are subjectivity and inconsistency in dividing the text and determining the structure of its composition, as in the study of surah al-Qa>ri‘ah by Cuypers, and an ignorance of the information about reasons for the revelations (asba>b al-nuzu>l) and Prophet’s explanation about verses. However, the application of this method can lead to a new interpretation of the Qur’an, namely by using the information in the Qur’an itself, indicators of wording around it (siya>q), and verse correlation (muna>saba>t). On the other hand, this method supports the authenticity and coherence of the Qur’anic text, which has become a debate among the Orientalists.